Open Educational Resources: The What, How, Why, and Who - Kris Helge (Academic Chairpersons Conference Proceedings, 2019)
Open educational resources are free, digitally available, valid and reliable textbooks, videos, syllabi, and other educational resources utilized to save students money. This session describes what open educational resources are, where to locate them, why to use them, and it reinforces their validity and reliability of use.
Keywords: open educational resources